2022
DOI: 10.1186/s12882-022-02932-2
|View full text |Cite|
|
Sign up to set email alerts
|

Elevated triglycerides and reduced high-density lipoprotein cholesterol are independently associated with the onset of advanced chronic kidney disease: a cohort study of 911,360 individuals from the United Kingdom

Abstract: Background Increased total cholesterol (TC), triglycerides (TG), low-density lipoprotein cholesterol (LDL-C), and decreased high-density lipoprotein cholesterol (HDL-C) concentrations, are established risk factors for cardiovascular morbidity and mortality; but their impact on the risk of advanced chronic kidney disease (CKD) is unclear. This study evaluates the association between the different lipid profiles and the onset of advanced CKD using a general population sample. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 33 publications
(44 reference statements)
0
19
0
Order By: Relevance
“…This study also revealed that apart from hyperglycemia and raised BP, as traditional risk factors of CKD, other components of MetS, including obesity, increased triglyceride, and reduced HDL-cholesterol are also reported to be important factors in new-onset CKD and subsequent disease progression in observational studies [ 61 , 62 , 63 ] and meta-analyses [ 48 , 64 , 65 ]. Targeting disturbances of renal energy metabolism is a promising approach to addressing the current epidemic of metabolic disease-induced renal diseases.…”
Section: Discussionmentioning
confidence: 75%
“…This study also revealed that apart from hyperglycemia and raised BP, as traditional risk factors of CKD, other components of MetS, including obesity, increased triglyceride, and reduced HDL-cholesterol are also reported to be important factors in new-onset CKD and subsequent disease progression in observational studies [ 61 , 62 , 63 ] and meta-analyses [ 48 , 64 , 65 ]. Targeting disturbances of renal energy metabolism is a promising approach to addressing the current epidemic of metabolic disease-induced renal diseases.…”
Section: Discussionmentioning
confidence: 75%
“…Recently, data from a large cohort study showed that elevated TG and reduced HDL-C levels were associated with the onset of advanced chronic kidney disease (CKD) [ 21 ]. In addition, the ratio of TG to HDL-C, which is associated with insulin resistance [ 22 ] and cardiovascular events, was found to be associated with the risk of CKD in the Japanese population [ 23 ], while another study showed that elevated TG/HDL-C was positively correlated with CKD development in Korean males but not females [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…• High-fat levels: people with membrane nephropathy frequently have high levels of both cholesterol (Cho) and triglycerides (TGs), which dramatically increase the risk of heart disease, owing mainly to impaired clearance and, to a lesser extent increased biosynthesis [13].…”
Section: Complicationsmentioning
confidence: 99%
“…• Chronic kidney disorders: Due to the patient's kidneys gradually losing function over time, they may eventually need dialysis or a kidney transplant [13,14].…”
Section: Complicationsmentioning
confidence: 99%